INOVASI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM - Citra Laillatul Mukharromah; Ahmad Marzuki; Achmat Mubarok; Achmad Yusuf (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT In the digital era, school principals are expected not only to manage educational institutions but also to drive change by fostering a professional learning environment for teachers. This condition can be observed at SMAN 1 Purwosari, where various leadership strategies have been implemented to strengthen the competencies of Islamic Religious Education (PAI) teachers. This study explores how leadership innovation is translated into school management practices and examines its contribution to teacher competency development. A qualitative approach was employed, utilizing interviews, observations, and documentation as the primary sources of data. The investigation focused on identifying teachers’ needs, implementing competency development programs, conducting instructional supervision, integrating educational technology, and evaluating ongoing initiatives. The findings reveal that teacher competency development was carried out through a planned and participatory leadership approach involving multiple stakeholders. Key innovations included needs-based planning, collaborative decision-making, continuous academic supervision, professional training programs, and the integration of digital media into classroom instruction. These initiatives contributed to improvements in the pedagogical, professional, social, and personal competencies of PAI teachers. In addition, the application of active learning methods and digital technologies created more interactive, contextual, and engaging learning experiences for students. Nevertheless, greater variation in instructional strategies remains necessary to further enhance student participation. Overall, the study highlights leadership innovation as a strategic factor in strengthening teacher competencies and improving the quality of learning within the school environment. ABSTRAK Dinamika pendidikan pada era digital menempatkan kepala sekolah tidak hanya sebagai pengelola lembaga, tetapi juga sebagai penggerak perubahan yang mampu menciptakan lingkungan belajar profesional bagi guru. Kondisi tersebut terlihat di SMAN 1 Purwosari, di mana berbagai strategi kepemimpinan dikembangkan untuk memperkuat kompetensi guru Pendidikan Agama Islam (PAI). Kajian ini menelusuri bagaimana inovasi kepemimpinan kepala sekolah diwujudkan dalam praktik pengelolaan sekolah serta dampaknya terhadap pengembangan kompetensi guru. Penelitian dilakukan melalui pendekatan kualitatif dengan memanfaatkan wawancara, observasi, dan dokumentasi sebagai sumber utama pengumpulan data. Fokus pengamatan diarahkan pada pemetaan kebutuhan guru, pelaksanaan program pengembangan kompetensi, supervisi pembelajaran, penggunaan teknologi pendidikan, dan evaluasi program yang telah berjalan. Temuan penelitian menunjukkan bahwa pengembangan kompetensi guru dilaksanakan melalui pola kepemimpinan yang terencana dan melibatkan berbagai pihak. Bentuk inovasi yang menonjol mencakup perencanaan berbasis kebutuhan, pengambilan keputusan secara kolaboratif, supervisi akademik yang berkelanjutan, penyelenggaraan pelatihan profesional, serta pemanfaatan media digital dalam proses pembelajaran. Implementasi berbagai langkah tersebut berkontribusi terhadap peningkatan kompetensi pedagogik, profesional, sosial, dan kepribadian guru PAI. Dampak lain yang terlihat adalah terciptanya pembelajaran yang lebih interaktif, kontekstual, dan menarik melalui penerapan metode aktif serta integrasi teknologi digital. Meskipun demikian, pengembangan variasi strategi pembelajaran masih diperlukan untuk mendorong partisipasi siswa yang lebih optimal. Dengan demikian, inovasi kepemimpinan kepala sekolah menjadi unsur strategis dalam penguatan kompetensi guru sekaligus peningkatan kualitas pembelajaran di sekolah.